On our feet: taking steps to challenge women's oppression: a handbook on gender and popular education workshops - Mackenzie, Liz (University of Western Cape. Centre for Adult & ContinuingEducation BellvilleZA, 1992)
Provides ideas for the preparation, planning, designing and running of a workshop on gender and women's oppression. Presents some key concepts and terms regarding gender; reports from Talking Gender Workshops, highlighting the everyday experiences of women living in Southern Africa; and exercises to assist in the development of strategies for action.